Sensory neuroecology and multimodal evolution across the genus Drosophila - Keesey, Ian W. (Frontiers in Ecology and Evolution, 2022)
The neural basis and genetic mechanisms for sensory evolution are increasingly being explored in depth across many closely related members of the Drosophila genus. This has in part been achieved due to the immense efforts towards adapting gene-editing technologies for additional, non-model species. Studies targeting both peripheral sensory variations, as well as interspecies divergence in coding or neural connectivity have generated numerous, tangible examples of how and where the evolution of sensory-driven animal behavior has occurred. Here we review and discuss studies that each aim to identify the neurobiological and genetic components of sensory system evolution to provide a comparative overview of the types of functional variations observed across both perceptual input and behavioral output. In addition, we examine the roles neuroecology and neuroevolution play in speciation events such as courtship and intraspecies communication, as well as those aspects related to behavioral divergence in host navigation or egg-laying preferences. Through the investigation of comparative, large-scale trends and correlations across diverse, yet closely related species within this highly ecologically variable genus of flies, we can begin to describe the underlying pressures, mechanisms and constraints that have guided sensory and nervous system evolution within the natural environments of these organisms.